Diet Supplementation with Polyphenol-Rich Salicornia ramosissima Extracts Protects against Tissue Damage in Experimental Models of Cerebral Ischemia. - García-Rodríguez, P.; Ma, F.; Río, C.D.; Romero-Bernal, M.; Najar, A.M.; Cádiz-Gurrea, M.L.; Leyva-Jimenez, F.J.; Ramiro, L.; Menéndez-Valladares, P.; Pérez-Sánchez, S.; Segura-Carretero, A.; Montaner, J. (Nutrients, 2022)
Strokes are the second most common cause of death worldwide and a leading cause of disability. Regular consumption of polyphenols has been shown to reduce the risk of suffering a cardiovascular event. For this reason, we have investigated the protective effect of Salicornia ramosissima, a seasonal halophyte that synthetizes high amounts of bioactive compounds, including polyphenols, in response to environmental stress. Aqueous, hydroalcoholic, and ethanolic extracts were prepared to investigate if dietary supplementation prior to ischemic challenge can prevent subsequent damage using two animal models. First, we screened the protective effect against hypoxia-reoxygenation in Drosophila melanogaster and observed that both ethanolic and hydroalcoholic extracts protected flies from the deleterious effects of hypoxia. Second, we confirmed the protective effect of S. ramosissima ethanolic extract against brain ischemia using the transient middle cerebral artery occlusion mice model. Four weeks of oral supplementation with the ethanolic extract before artery occlusion reduced infarct volume and lowered the plasma levels of the DNA peroxidant product 8-hydroxydeoxyguanosine. Phytochemical profiling of S. ramosissima ethanolic extract revealed 50 compounds. Thus, it represents a valuable source of bioactive compounds that show promising disease-modifying activities and could be further developed as an effective food supplement for the prevention or treatment of neurovascular disorders.